Caracterização da fauna de Dytiscidae (Insecta: Coleoptera: Adephaga) da várzea do rio Solimões/Amazonas - Braga, Rafael Benzi. (UFRJ, 2008)
[PT] Com mais de 3.000 espécies descritas, os besouros da família Dytiscidae, de distribuição cosmopolita, constituem a segunda maior família da subordem Adephaga. No Brasil ocorrem aproximadamente 290 espécies, distribuídas em 36 gêneros. Para a região amazônica, assim como para toda a Região Neotropical, as informações de cunho biológico são raras e fragmentadas. Com o objetivo de caracterizar a fauna de Dytiscidae da Várzea do Rio Amazonas, foram feitas coletas em 27 ao longo de sua calha. Para tanto, utilizaram-se dois métodos de coleta: com uma rede do tipo puçá e através de armadilhas luminosas. Devido à grande quantidade de material e a falta de bibliografia sobre o assunto apenas os indivíduos adultos foram utilizados no trabalho. Foram coletados 12.212 exemplares de Dytiscidae, divididos em 39 táxons terminais, dos quais 27 foram identificados em nível específico e sete são espécies não descritas. Os 12 táxons restantes não puderam ser identificados em nível específico. Todos os táxons terminais foram descritos, medidos, tiveram suas estruturas desenhadas, e foram incluídos numa chave de identificação.[EN] The Dytiscidae is a family of water beetles with more than 3,000 described species of cosmopolite distribution, and they constitute the second largest family of the suborder Adephaga. In Brazil there are about 290 species distributed in 36 genera. In the Amazon region, as well as in the whole Neotropical Region, this fauna is poorly known. The information on genera, species, their distribution and biology is scarce. The purpose of this work is to survey the occurrences of Dytiscidae genera in the “várzea” of the Amazone river, in the Brazilian territory. The collecting area of the Amazon river has about 7,050,000 km2, and about 50,000-60,000 km2 of this area constitutes the “várzea” ecosystem, which presents a great aquatic productivity. The material was collected with hand-net and light trap from 27 localities in várzea areas. Due to the great amount of material and the bibliography lack on the subject, only the adult individuals were used in the work. 12,212 units of Dytiscidae were collected and divided into 39 terminals táxons, of these táxons 27 had been identified in specific level, seven are not described species, the 12 táxons remaining could not be identified in specific level. All táxons terminals had been described, measured, its structures drawn and it was created a key of identification for them.